Effect of Dietary Tryptophan on Growth, Intestinal Microbiota, and Intestinal Gene Expression in an Improved Triploid Crucian Carp - Fu, Yawei; Liang, Xiaoxiao; Li, Donghua; Gao, Hu; Wang, Yadong; Li, Wenting; Xu, Kang; Hu, Fangzhou (Frontiers in Nutrition, 2021)
Tryptophan (Trp) has received increasing attention in the maintenance of intestinal function. In this study, improved triploid crucian carp (ITCC) fed diets containing 6.35 g kg-1 Trp had higher average daily weight gain and improved villus height (VH) and crypt depth (CD) in the intestine compared to the control group. To elucidate the potential mechanisms, we used RNA sequencing (RNA-seq) to investigate changes in the intestinal transcriptome and 16S rRNA gene sequencing to measure the intestinal microbiota in response to 6.35 g kg-1 Trp feeding in ITCC. Dietary Trp altered intestinal gene expression involved in nutrient transport and metabolism. Differentially expressed genes (DEGs) were highly enriched in key pathways containing protein digestion and absorption and the AMPK signaling pathway. 16S rRNA sequencing showed that 6.35 g kg-1 Trp significantly increased the abundance of the genus Cetobacterium, and the Firmicutes / Bacteroidetes ratio at the phylum level (P < 0.05). In addition, bacterial richness indices (Simpson index) significantly increased (P < 0.05) community evenness in response to 6.35 g kg-1 Trp. In conclusion, appropriate dietary Trp improves the growth performance, and influences the intestinal flora of ITCC. This study might be helpful to guide the supply of dietary exogenous Trp in ITCC breeding.